COMPUTER GRAPHICS USED TO OVER CONSTRAINED MECHANISMS’ MOBILITY - Ionut GEONEA; Simona-Mariana CRETU (Journal of Industrial Design and Engineering Graphics, 2019)
The objective of this study is the use of computer graphics as teaching methodology in the field of robotics, focused on over constrained mechanisms’ mobility. Because the analytical methods applied to calculate the mobility of robots have a high mathematical level, but also because certain parameters of over constrained mechanisms are usually determined by structural methods, we have used computer graphics in ADAMS in the teaching process, so that students easily understand the connection between theory and practice, and then solve the engineering applications.